Disabled Capitalists: Exploring the Intersections of Disability and Identity Formation in the World of Work - Galer, Dustin (Disability Studies Quarterly, 2012)
Many people with disabilities share the mainstream ethos that participation in the competitive workforce constitutes a primary feature of their identity. While unpaid work may fulfill the desire to be productive and provide a sense of purpose and contribution, the cultural imperative to achieve personal autonomy partly through material independence situates paid employment at the centre of personal identity formation. While disability activists struggle to carve out an empowered collective identity instilled with rights-based protections, many people with disabilities identify with the liberal individualism upon which participation in the capitalist labour market is largely based. Individuals with disabilities seek not simply to shrug off an identity defined by burden, but to claim an identity marked by self-fulfillment. Within the world of paid work, then, tension and compatibility co-exist regarding the nature and value of identity development for people with disabilities. Keywords: disability, work, employment, identity, identity politics, disability activism